Operationalizing collaborative problem-solving skills: A framework for assessment and development in the digital age - Sergiu MAXIM (Studia Universitatis Babes-Bolyai, 2023)
This article delves into the operationalization of collaborative problem-solving (CPS) skills, focusing on the essential aspects required to effectively apply CPS in the modern digital age. The article emphasizes the growing significance of CPS skills as technology-based work and the automation of routine tasks demand proficiency in addressing non-routine, complex challenges. To enable successful CPS, a new set of skills including information literacy, divergent thinking, and problem-solving, both individually and collaboratively, are explored. The article investigates the strategies and approaches employed by individuals and teams when engaging in collaborative problem solving, with an emphasis on knowledge sharing and skill pooling. The study highlights the criticality of CPS as an invaluable skill set, enabling individuals to effectively collaborate and overcome intricate problems. Moreover, as contemporary work environments increasingly rely on successful group problem solving, the significance of operationalizing CPS is expected to continue growing in the future.